2020
DOI: 10.1371/journal.pntd.0008077
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection and identification of Leishmania DNA and blood meal analysis in Phlebotomus (Larroussius) species

Abstract: Background Phlebotomus (Larroussius) perniciosus and Canis familiaris are respectively the only confirmed vector and reservoir for the transmission of Leishmania (L.) infantum MON-1 in Tunisia. However, the vector and reservoir hosts of the two other zymodemes, MON-24 and MON-80, are still unknown. The aim of this study was to analyze the L. infantum life cycle in a Tunisian leishmaniasis focus. For this purpose, we have focused on: i) the detection, quantification and identification of Leishmania among this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 71 publications
(100 reference statements)
0
15
0
Order By: Relevance
“…Our results showed that P. perniciosus was highly susceptible for all three L. (S.) tarentolae strains studied. Although several studies have reported the broad host range of P. perniciosus [54][55][56], its willingness to feed on geckos has not been recorded yet. Leishmania promastigotes isolated from P. perniciosus, even in females collected in Mediterranean sites where Se.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that P. perniciosus was highly susceptible for all three L. (S.) tarentolae strains studied. Although several studies have reported the broad host range of P. perniciosus [54][55][56], its willingness to feed on geckos has not been recorded yet. Leishmania promastigotes isolated from P. perniciosus, even in females collected in Mediterranean sites where Se.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of bloodmeals from phlebotomines using partial sequences from PCR products of the mtDNA cyt b gene is suitable and widely used for this purpose ( Jiménez et al 2013 , Carvalho et al 2017 , Pereira Junior et al 2019 , Doe et al 2020 , Leão et al 2020 , Remadi et al 2020 , Lozano-Sardaneta et al 2021 , Rodrigues et al 2021 , Torchitte et al 2020 ). Six vertebrate species were found to be blood feeding sources of Ny.…”
Section: Discussionmentioning
confidence: 99%
“…This was the case of the emerging VL foci located in the arid bioclimatic zone of Central Tunisia that evidenced a high mobilization of water resources recent years [ 12 , 14 ]. In these emerging foci of high VL incidence, several entomological surveys have been carried out showing L. infantum infection of several Laroussius species, notably P. perniciosus , P. perfiliewi , and P. longicuspis [ 15 , 16 , 17 ], but also showed L. infantum infection of Phlebotomus papatasi [ 15 , 17 ] and Sergentomyia minuta [ 15 ]. These studies have also highlighted the role of P. perfiliewi in these particular foci [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In these emerging foci of high VL incidence, several entomological surveys have been carried out showing L. infantum infection of several Laroussius species, notably P. perniciosus , P. perfiliewi , and P. longicuspis [ 15 , 16 , 17 ], but also showed L. infantum infection of Phlebotomus papatasi [ 15 , 17 ] and Sergentomyia minuta [ 15 ]. These studies have also highlighted the role of P. perfiliewi in these particular foci [ 15 , 16 ]. To our knowledge, no information is available on L. infantum infection rate of phlebotomine sandflies in Northern VL endemic areas of low incidence where P. perniciosus and P. perfiliewi are known to be sympatric species [ 18 ].…”
Section: Introductionmentioning
confidence: 99%